2019
DOI: 10.1002/admi.201901528
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Ferroelectric Phase in Undoped HfO2 Films Deposited by Sputtering

Abstract: Thin film metal-insulator-metal capacitors with undoped HfO2 as the insulator are fabricated by sputtering from ceramic targets and subsequently annealed. The influence of film thickness and anneal temperature is characterized by electrical and structural methods. After annealing, the films show distinct ferroelectric properties. Grazing incidence x-ray diffraction measurements reveal a dominant ferroelectric orthorhombic phase for thicknesses in the 10-50 nm range and a negligible non-ferroelectric monoclinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 23 publications
5
25
0
Order By: Relevance
“…4,5 Recently, HfO 2 has attracted extensive scientific interest as a promising oxide material, especially for the unique ferroelectricity in HfO 2 -based films. 6 Ferroelectricity in Si, Y, and Al doped HfO 2 films, [6][7][8][9][10] even undoped HfO 2 films, 11 has been reported on. However, there is little research on HfO 2 ceramics, and no ferroelectricity has been reported in HfO 2 -based ceramics.…”
Section: Introductionmentioning
confidence: 95%
“…4,5 Recently, HfO 2 has attracted extensive scientific interest as a promising oxide material, especially for the unique ferroelectricity in HfO 2 -based films. 6 Ferroelectricity in Si, Y, and Al doped HfO 2 films, [6][7][8][9][10] even undoped HfO 2 films, 11 has been reported on. However, there is little research on HfO 2 ceramics, and no ferroelectricity has been reported in HfO 2 -based ceramics.…”
Section: Introductionmentioning
confidence: 95%
“…6 For PVD samples, the oxygen vacancies likely take this function. 4 In HAXPES spectra, oxygen vacancies V 0 manifest themselves as a small Hf 3þ component at the low binding energy side of Hf 4f spectra (see Fig. 3).…”
mentioning
confidence: 97%
“…Oxygen vacancies are recognized as those defects, which have a positive impact on the stabilization of the ferroelectric orthorhombic phase in undoped HfO 2 . [4][5][6] Here, we present a comparative study of both ALD-and PVD-grown HfO 2 thin films interfaced with TiN bottom/top electrodes (BE/TEs) integrated into TiN/HfO 2 /TiN capacitors. We apply hard x-ray photoelectron spectroscopy (HAXPES) as an equally depth-sensitive and element-specific chemical characterization technique, 7,8 which allows us to gain a comprehensive picture of the chemical state of the HfO 2 layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been believed that the observation of the ferroelectricity in hafnia films were contributed by a formation of a non-centrosymmetric Pca2 1 orthorhombic phase [ 19 , 20 ]. The ferroelectricity was also observed in the undoped HfO 2 film [ 21 ], but incorporating the optimized dopants seems to make the phase transformation more effective and easier.…”
Section: Introductionmentioning
confidence: 99%